Interelasi indeks pasar sektoral dalam kondisi tingkat bunga tertinggi - Raphajirsy Berthveight Akerina; Syalwa Nabilla Eka Putri (Yayasan Widyantara Nawasena Raharja, 2023)
Interest rate policy is an important factor for controlling the inflation rate as well as controlling economic growth. The objectives of this study are: first, to examine the relationship between interest rates and market indexes; second, the interrelationship of market indexes during interest rate issues. The sample of this study is 12 market indexes during the observed period 24 October 2022 to 28 April 2023. This study finds that several market indices experienced an increase and several market indices also experienced a decrease when interest rates were at their highest levels. Other important findings also show that changes in interest rates tend not to have a significant impact on market indices, especially during the observation period of this study. Throughout the observation period, consistently, this study finds that the non-primary consumer goods sector consistently did not correlate with the health sector, the financial sector consistently did not correlate with the health sector, and the health sector consistently did not correlate with the technology sector.